2012
DOI: 10.3389/fonc.2012.00005
|View full text |Cite
|
Sign up to set email alerts
|

K63-Linked Ubiquitination in Kinase Activation and Cancer

Abstract: Ubiquitination has been demonstrated to play a pivotal role in multiple biological functions, which include cell growth, proliferation, apoptosis, DNA damage response, innate immune response, and neuronal degeneration. Although the role of ubiquitination in targeting proteins for proteasome-dependent degradation have been extensively studied and well-characterized, the critical non-proteolytic functions of ubiquitination, such as protein trafficking and kinase activation, involved in cell survival and cancer d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 198 publications
(257 reference statements)
2
85
0
Order By: Relevance
“…It has been suggested that TRAF6 induces the activation of IKK complex and TAK1-TAB2 complex via K63-linked polyubiquitin (12-14). TRAF6, an E3 ubiquitin ligase, catalyzes synthesis of K63-linked polyu- biquitination of IKKγ and TRAF6 itself (12). The K63-linked polyubiquitin chains function as a scaffold to recruit the TAK1-TAB2 complex and IKK complex through binding to TAB2 and IKKγ, respectively (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that TRAF6 induces the activation of IKK complex and TAK1-TAB2 complex via K63-linked polyubiquitin (12-14). TRAF6, an E3 ubiquitin ligase, catalyzes synthesis of K63-linked polyu- biquitination of IKKγ and TRAF6 itself (12). The K63-linked polyubiquitin chains function as a scaffold to recruit the TAK1-TAB2 complex and IKK complex through binding to TAB2 and IKKγ, respectively (13).…”
Section: Discussionmentioning
confidence: 99%
“…RTA, encoded by the immediate-early gene ORF50, is a critical switch molecule for initiating lytic replication. In canonical NF-κB signaling, the NF-κB transcription factor, which is a heterodimer of p50 and p65/RelA, is retained in the cytosol by interaction with IκBα (12). IκBα is further regulated by the IκB kinase (IKK) complex, consisting of IKKα, IKKβ and IKKγ/NEmO.…”
Section: Introductionmentioning
confidence: 99%
“…Lys 63 -linked ubiquitylation is sometimes required for signaltransduction processes, whereas Lys 48 -linked ubiquitylation typically leads to proteasome degradation (29). Therefore, we created Ub K48-only and K63-only mutants to investigate IpaH4.5-mediated TBK1 ubiquitylation.…”
Section: Ipah45 Induces Tbk1 Degradation By K48-linked Ubiquitinationmentioning
confidence: 99%
“…1). The assembly step of activated receptor complexes involves TRAF2 and cellular inhibitor of apoptosis protein 1/2 (cIAP1/2)-mediated K63-linked ubiquitination of several of the components, including TRAF2, TRAF6, TAK1, RIP1, and NF-kB essential modulator (NEMO), which facilitates protein-protein interactions and the assembly of the signaling complexes (10)(11)(12)(13)(14). The main enzyme that removes polyubiquitin chains from the above proteins is the cylindromatosis tumor suppressor cylindromatosis deubiquitinase (Cyld; refs.…”
Section: Interplay Between Nf-kb and Jnk Signaling Pathwaymentioning
confidence: 99%